‘Teach-back’ is a simple communication tool that improves disease knowledge in people with chronic hepatitis B – a pilot randomized controlled study - Sophie Tran; Gabrielle Bennett; Jacqui Richmond; Tin Nguyen; Marno Ryan; Thai Hong; Jessica Howell; Barbara Demediuk; Paul Desmond; Sally Bell; Alexander Thompson (BMC Public Health, 2019)
Abstract Background The low diagnosis rate and poor access to clinical care among people with CHB is a major barrier to reducing HBV-related morbidity and mortality in Australia. One explanation for this is a lack of disease-specific knowledge among people living with CHB. Health literacy has been shown to be important for maximising engagement with medical care and adherence to recommended management. The ‘teach-back’ communication strategy has been shown to improve patient understanding in other clinical areas. This study aims to assess disease-specific knowledge; and evaluate the efficacy of the teach-back strategy for improving HBV knowledge, compared to a standard medical consultation. Method A randomized pilot study was conducted between February and June 2017. Participants were recruited from the liver clinic at an inner-city tertiary hospital. English-speaking patients aged ≥18 years and diagnosed with CHB were eligible for the study. Participants were randomised to a control group (medical specialist appointment) and intervention group (teach-back). Knowledge was assessed at baseline, immediately post-intervention and at one month using a validated questionnaire. Participants in the intervention group received a one-on-one teach-back session about CHB. The main outcome measure was a combined knowledge score of the domains assessed – transmission, natural history, epidemiology and prevention and clinical management. Results Seventy participants were recruited (control n = 32, teach-back n = 38). Mean baseline knowledge score was 19.1 out of 23 with 55 (79%) participants scoring ≥17.3 (defined as high knowledge) (7). Sub-analysis of CHB knowledge domains identified focal deficits concerning transmission and whether HBV is curable. Knowledge scores were found to be positively associated with English proficiency and antiviral treatment experience (p < 0.05). Teach-back was associated with a significant increase in CHB knowledge at early recall (22.5 vs 18.7, p < 0.001) and at 1-month follow-up (21.9 vs 18.7, p < 0.001); there was no improvement in CHB knowledge associated with standard clinical consultant (early recall: 19.6 vs 19.4, p = 0.49, one-month follow-up: 19.5 vs 19.4, p = 0.94). Conclusion In a tertiary hospital liver clinic population, baseline knowledge about CHB was good, but there were focal deficits concerning transmission and potential for cure. Teach-back was associated with improvement in CHB knowledge and it is a simple communication tool suitable for incorporation into a standard medical consultation.